The inheritance of a Mesozoic landscape in western Scandinavia - Fredin, Ola; Viola, Giulio; Zwingmann, Horst; Sørlie, Ronald; Brönner, Marco; Lie, Jan-Erik; Grandal, Else Margrethe; Müller, Axel Bernd; Margreth, Annina; Vogt, Christoph; Knies, Jochen (Nature Communications, 2017)
Source at http://dx.doi.org/10.1038/ncomms14879 In-situ weathered bedrock, saprolite, is locally found in Scandinavia, where it is commonly thought to represent pre-Pleistocene weathering possibly associated with landscape formation. The age of weathering, however, remains loosely constrained, which has an impact on existing geological and landscape evolution models and morphotectonic correlations. Here we provide new geochronological evidence that some of the low-altitude basement landforms on- and offshore southwestern Scandinavia are a rejuvenated geomorphological relic from Mesozoic times. K-Ar dating of authigenic, syn-weathering illite from saprolitic remnants constrains original basement exposure in the Late Triassic (221.3±7.0–206.2±4.2 Ma) through deep weathering in a warm climate and subsequent partial mobilization of the saprolitic mantle into the overlying sediment cascade system. The data support the bulk geomorphological development of west Scandinavia coastal basement rocks during the Mesozoic and later, long-lasting relative tectonic stability. Pleistocene glaciations played an additional geomorphological role, selectively stripping the landscape from the Mesozoic overburden and carving glacial landforms down to Plio–Pleistocene times. Saprolite K-Ar dating offers unprecedented possibilities to study past weathering and landscape evolution processes.